Midwife’s Role in the Mother-to-Child Transmission Prevention Program in Primary Health Care in Yogyakarta - Meilani, Niken; Setiyawati, Nanik; Barasa, Sammy Onyapidi (Kesmas, 2019)
Curing and eradicating Human Immunodeficiency Virus (HIV)/Acquired Immunodeficiency Syndrome (AIDS) are to the core principles of the United Nations’ Sustainable Development Goals (SDGs). The incidence of HIV in the world remains high. Although midwives play a pivotal role in PMTCT implementation, the factors associated with midwives’ role in its implementation are not well understood. The aim of this study was to determine factors associated with midwives’ role in implementation of PMTCT. This study used a cross-sectional design. The subjects were 80 midwives at 14 primary health care in Yogyakarta City, Indonesia. The study was conducted from April to August 2017. Data were analyzed through univariate, bivariate with chi-square and Fisher’s exact test, multivariate with logistic regression. The results showed that 47.5% of midwives were in the poor category regarding implementation of PMTCT. Information availability through socialization (p-value = 0.047) and knowledge level (p-value = 0.016) were found to be related to PMTCT implementation. There was no relationship between age, length of work, education level, marital status, availability of information, midwife’s attitude, perception of the availability of facilities and institutional support with midwife behavior in PMTCT implementation. Multivariate analysis showed that level of knowledge was the most dominant factor affecting PMTCT implementation (OR:6.2; CI 95% = 1.8-21.4). We recommend that efforts should be made to continuously improve the knowledge of midwives on PMTCT implementation through peer support and training in order to achieve sustainable development goals.